FoamPi: An open-source raspberry Pi based apparatus for monitoring polyurethane foam reactions. (October 2022) - Wright, Harry C.; Cameron, Duncan D.; Ryan, Anthony J.
Graphical abstract: Abstract: Adiabatic temperature rise is an important method for determining isocyanate conversion in polyurethane foam reactions as well as many other exothermic chemical reactions. Adiabatic temperature rise can be used in conjunction with change in height and mass measurements to gain understanding into the blowing and gelling reactions that occur during polyurethane foaming as well as give important information on cell morphology. FoamPi is an open-source Raspberry Pi device for monitoring polyurethane foaming reactions. The device effectively monitors temperature rise, change in foam height as well as changes in the mass during the reaction. Three Python scripts are also presented. The first logs raw data during the reaction. The second corrects temperature data such that it can be used in adiabatic temperature rise reactions for calculating isocyanate conversion; additionally this script reduces noise in all the data and removes erroneous readings. The final script extracts important information from the corrected data such as maximum temperature change and maximum height change as well as the time to reach these points. Commercial examples of such equipment exist however the price (>£10000) of these equipment make these systems inaccessible for many research laboratories. The FoamPi build presented is inexpensive (£350) and test examples are shown here to indicate the reproducibility of results as well as precision of the FoamPi.